DEBT POLICY, SALES GROWTH, TAX AVOIDANCE: THE MODERATING ROLE OF INDEPENDENT COMMISSIONERS - Arie Rizky Amalia; Amrie Firmansyah (International Journal of Contemporary Accounting, 2022)
This study examines the effect of debt policy and sales growth on tax avoidance. In addition, this study examines the role of the independent commissioner as a moderating variable in the relationship between the independent and dependent variables. The method employed in this study is quantitative. This study uses secondary data with the annual financial statements of mining sector companies listed on the Indonesia Stock Exchange for 2018-2020. Research data is sourced from www.idx.co.id and the company's official website. Based on purposive sampling, the total sample of this study resulted in 103 observations. The data analysis technique used is multiple linear regression with a cross-section, namely Ordinary Least Squares (OLS). The results of this study suggest that debt policy is negatively associated with tax avoidance, while sales growth is not associated with tax avoidance. This study also suggests that independent commissioners cannot moderate the association between debt policy and tax avoidance. Also, independent commissioners could not moderate the association between sales growth and tax avoidance. This research indicates that the Indonesia Financial Services Authority needs to improve policies related to the arrangement of independent commissioners in publicly listed companies regarding protecting shareholders in the capital market and improving corporate governance listed on the Indonesia Stock Exchange.